173k views
0 votes
F(x) = x^2 - 5

g(x) = 4x - 4

Find (f-g) (5)

4

-5

-4

5

User Bmovement
by
6.1k points

2 Answers

2 votes

Answer:

4

Explanation:

f(x) = x^2 - 5

g(x) = 4x - 4

(f-g) (x)= x^2 - 5 - (4x - 4)

Distribute the minus sign

= x^2 - 5 - 4x + 4

= x^2 -4x-1

Let x = 5

(f-g) (5) = 5^2 -4(5) -1

=25 - 20 -1

=5-1

=4

User Enrique Flores
by
6.1k points
0 votes

Answer:

The correct answer option is: 4.

Explanation:

We are given the following two functions and we are to find the value of
( f - g ) ( 5 ):


f(x) = x^2 - 5


g(x) = 4x - 4

Finding
( f - g ) ( x ):


( f - g ) ( x )
= (x^2-5)-(4x-4) = x^2-4x-5+4


( f - g ) ( x ) = x^2-4x-1

So,
( f - g ) ( 5 ) = (5)^2-4(5)-1 = 4

User AlexGuevara
by
5.9k points